Development of SISTANA-based LKPD to enhance understanding of volcanic disaster mitigation at elementary schools - Misbahuddin, Hajir; Aditia Wiguna, Frans (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The limitation of students' understanding of disaster mitigation led the researchers to conduct a study that combined two previous studies, resulting in a new finding called Sistana. This research aimed to describe the suitability, effectiveness, and student response to the learning media in the form of Sistana-Based Student Worksheets (LKPD) in enhancing their understanding of disaster mitigation during the 6th-grade Social Studies class in Elementary School. The development model utilized by the researchers was the 4D model, which consists of four main stages: define, design, develop, and disseminate. The validation results by material experts showed a percentage of 80% as "valid." The media experts obtained a percentage of 84% as "valid," while the evaluation experts scored 80% as "valid." Furthermore, the results of the trial showed that the students' average pretest score was 43.1, and their posttest score was 88.1, indicating an improvement of 45 points. Finally, the student's assessment of the use of LKPD Sistana resulted in a 92% "very good" response rate. Therefore, it can be concluded that the developed LKPD Sistana is relevant and engaging as a learning medium to enhance students' understanding of disaster mitigation.